A Simple Method to Extract Whole Apolipoproteins for the Preparation of Discoidal Recombined High Density Lipoproteins as Bionic Nanocarriers for Drug Delivery - Wenli Zhang; Ji Wang; Junting Jia; Liang Chen; Zimei Wu; Jianping Liu (Frontiers Media S.A., 2015)
Purpose: To develop a simple method to extract the whole apolipoproteins (apo) including apoA-I in native high density lipoproteins (HDLs) and prepare discoidal Tanshinone IIA-loaded reconstituted HDL (TA-rHDLs) as a dual functional drug delivery system with plaque-site target and therapeutic promises in atherosclerotic lesions. Methods: A method based on isoelectric precipitation coupled with organic solvent precipitation was developed to isolate the whole apolipoproteins (apos). TA-rHDLs were prepared by incubating the resultant apos with liposomes and the incubation conditions were optimized using fluorescence quenching experiment. TA-rHDLs were characterized in terms of size, zeta potential, morphology, interaction between lipid and apos,  safety, and bionic function. Results: The extraction results showed that the yield of the HDL apos was 82.4%, with 59% being apoA-I type, similar ratio of apoA-I in the native apos. TA-rHDL prepared were disc-like with an average diameter of 157.6 ± 4.8 nm, zeta potential of -20.90 ± 0.15 mV, and entrapment efficiency of (90.13 ± 1.4) %. The interaction between the lipids and apos was electrostatic and hydrophobic force and was associated with amino acid sequence. Haemolysis and cytotoxicity assays showed good biocompatibility of TA-rHDL. Sterol efflux assay from macrophages mediated by TA-rHDLs and structure remodeling behavior from discs to spheres proved that TA-rHDL could resemble the biological activity of native nascent HDL irrespective of the size. Conclusions: The simple approach to isolate apos may provide a convenient and economical resource to support the development of rHDL as a potential targeting nanocarrier for lipophilic cardiovascular drugs. This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.